Penggunaan Escavator Untuk Galian Tie Beam dan Pile Cap di Proyek Paddel Court Pondok Indah - Hutagaol, Kerlima; Hartanto, Sri; Nasution, Muhammad Ricko; Johnatan, Jorgy; Evani, Meliana Nur (LPPM Institut Pendidikan Nusantara Global, 2025)
The use of heavy equipment in construction work has become a key solution to improving project execution efficiency and effectiveness. One critical phase in construction is excavation for substructure elements such as tie beams and pile caps, which require precision and speed during implementation. This study discusses the application of a mini excavator for substructure excavation work in the Paddle Court development project located at Plaza 6 Pondok Indah. The aim of the study is to evaluate how far the mini excavator can offer advantages in terms of time, cost, labor, and accuracy of the work compared to conventional manual methods. The methodology includes direct field observation, visual documentation, and qualitative analysis of productivity and challenges encountered during implementation. The results show that using a mini excavator can accelerate execution time by up to 60% and significantly reduce labor needs. However, challenges such as limited maneuvering space in tight areas and the need for strict supervision to maintain excavation accuracy were also identified. These findings form the basis for recommendations to contractors in selecting excavation methods based on site conditions, project capacity, and time urgency. Therefore, the use of a mini excavator is an effective solution to enhance project productivity, particularly for large-volume substructure work in areas with adequate working space. This research is expected to serve as a technical reference for similar future construction projects.